Pépinières et Centres d’appui en Algérie : -Entre une volonté déterminée des pouvoirs publics et un vécu contrarié - Gherras Nahla (Journal of North African Economies, 2025)
The interest in examining the situation of business nurseries and support centers as incubators, supervising SMEs/SMIs, is to know to what extent these local structures have enabled project leaders to resolve all the difficulties encountered during their businesses. To do this, we favored field work by organizing direct meetings with the officials in charge of these structures at the level of the chief towns of eastern Algeria. Chief towns bringing together both a business nursery and a support center. These meetings, in the form of interviews, allowed managers to highlight the difficulties encountered during their management mission. Among these constraints we note financing, the distance of the headquarters from the centers of the chief towns, making any movement of project leaders difficult; Finally, the managers of these incubators do not have the entrepreneurial training required to instill a real dynamic of supervision of project leaders.